Ferromagnetic resonance in nanomagnetic metal core and noble metal shell systems - Bala, Tanushree; Enoki, Toshiaki; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2007)
The change in the line widths in the ferromagnetic resonance (FMR) spectra of Co and Ni nanoparticles upon shell formation with noble metals like gold or silver are described. The NicoreAgshell, CocoreAgshell, and CocoreAushell nanoparticles were prepared by a simple transmetallation reaction between the Co and Ni nanoparticles and the Ag+ or AuCl−4 ions. It is revealed that the FMR line width decreases upon Ag shell formation whereas it increases upon core–shell composite formation with Au. Several probable explanations such as the differences in size distributions before and after the reaction or the changes occurring in shape anisotropy of the particles due to the shell formation or the different extents of electronic interaction between the core and shell materials have been offered for this observation.
Keywords: Fmr Study; Line Width Comparison; Magnetic Core-Noble Metal Shell Nanoparticles

Foam based synthesis of metal carbonates: establishing the role of spatial confinement for obtaining interesting morphologies - Bala, Tanushree; Sanyal, Ambarish; Pant, Jayashree; Bhagavatula L. V. Prasad (Journal of Computational and Theoretical Nanoscience, 2012)
The crystallization of different carbonates namely lead carbonate, cadmium carbonate and strontium carbonate in aqueous foam stabilized by the surfactant sodium dodecyl sulphate (SDS) by a method of cation entrapment is described. Reaction of ammonium carbonate with the respective cations electrostatically entrapped in the foam results in the formation of minerals, possibly in the Plateau border and Plateau junction regions of the foam. The unusual morphology of the crystals obtained from foam based synthetic method as compared to the crystals prepared in aqueous solution shows the utility of the template for the growth of crystals with an unusual morphology due to constrained environment. The materials are well characterized using TEM, SEM, EDAX and FTIR techniques. The large interfacial area of the liquid lamellae in the foam provides a striking possibility for the large-scale synthesis for not only minerals but also other nanoscale materials.

Facile method for the synthesis of Co-core Au-shell nanohybrid - Sardar, Debasmita; Neogi, S. K.; Bandyopadhyay, Sanjoy; Satpati, Biswarup; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal Of Chemistry, 2014)
Heterostructured Co-Au core-shell nanoparticles have been synthesized by reducing AuCl4- ions on cobalt nanoparticles after a minor but effective modification of cobalt surface by an amine. The core shell morphology is emphatically confirmed by thorough investigation through UV-Vis spectroscopy, X-ray photoelectron spectroscopy (XPS), and transmission electron microscopic analysis (TEM). The chemical composition and topography were determined using STEM-HAADF analysis and EFTEM imaging. Fourier transform infrared (FTIR) spectroscopy confirms the surface modification of Co nanoparticles and the interactions involved between the ligands and the core and shell metals at various steps of the synthetic process. The magnetic properties confirm the material to be superparamagnetic in nature.

Facile synthesis of Al2O3-Pt nanocomposite and its catalytic activity - Das, Subhasis; Bordoloi, Ankur; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (Materials Research Express, 2017)
Pt nanoparticles were synthesized on gamma-alumina support in presence of oleic acid which was found to prevent clustering of Pt nanoparticles on the support. Various percentage of Pt loading on the alumina changed the catalytic activity for preferential oxidation of CO at relatively low temperature in H-2 rich stream. Pt nanoparticles when synthesized in absence of oleic acid, were all clustered and did not have any catalytic activity. The presence of oleic acid promoted stability preventing agglomeration of Pt nanoparticles. The catalyst thus prepared was characterized thoroughly and their catalytic activity was studied in details.

Facile synthesis of ZnO-Ag nanocomposite and its photocatalytic activity - Sardar, Debasmita; Maity, Jayeta; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (Materials Research Express, 2017)
The evolution of photoactive hybrid materials (e.g. noble metal-semiconductor) has resulted in heterogeneous photocatalysis. We report a facile route for the synthesis of ZnO-Ag nanocomposites with varying percentage of loading of the noble metal, expecting a great boost in the photocatalytic behavior of ZnO. The as prepared material was thoroughly characterized by UV-Vis, FTIR, TEM, FESEM, XRD, XPS analyses. The photocatalytic activities of the nanocomposites have been assessed from the ability to degrade methylene blue dye in aqueous solution. The results suggest that incorporation of Ag nanoparticles on the surface of ZnO particles can enhance catalytic activity in comparison to pure ZnO particles under visible light by minimizing the recombination of photogenerated electron-hole pairs.